The Control of Human Immunosystem by Using Paeony Root Drug - Hideo Tsuboi; Muhaimin Rifa’i; Khaled Hossain; Izumi Nakashima; Haruhiko Suzuki (Journal of Tropical Life Science, 2010)
Paeoniflorin (PF), isolated from paeony root, has been used as a herbal medicine for more than 1200 years in China, Korea and Japan for its anti-allergic, anti-inflamatory and immunoregulatory effects. In this study, we found that PF induces apoptosis in both murine T-lineage cells and human T-cell leukemia Jurkat cells. This apoptosis was mediated through the reduction of mitochondrial membrane potential, activation of caspase and fragmentation of DNA. Interestingly, PF induced generation of reactive oxygen species (ROS) and a reducing agent, dithiothreitol (DTT), and a ROS scavenger, N-acetyl cysteine (NAC), successfully attenuated the PF-induced apoptosis. Additionally, PF induced the phosphorylation of three mitogen-activated protein (MAP) family kinases, extracellular signal-regulated kinase, c-Jun amino-terminal kinase (JNK) and p38 MAP kinase. Curcumin, an anti-oxidant and JNK inhibitor, inhibited PF-induced apoptosis, suggesting the possible involvement of curcumin-sensitive JNK or other redox-sensitive elements in PF-induced apoptosis. These results partially explain the action mechanism of PF-containing paeony root as a herbal medicine.Keywords: paeoniflorin; paeony root; apoptosis; reactive oxygen species (ROS); redox; CD8+ CD122+ regulatory T cells